2018
DOI: 10.3390/ijerph15122737
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Spousal Violence Victimization and Perpetration, Physical Illness, and Health Risk Behaviours among Women in India

Abstract: The aim of this study was to assess the association between lifetime spousal violence victimization, spousal violence perpetration, and physical health outcomes and behaviours among women in India. In the 2015–2016 National Family Health Survey, a sample of ever-married women (15–49 years) (N = 66,013) were interviewed about spousal violence. Results indicate that 29.9% of women reported lifetime spousal physical violence victimization and 7.1% lifetime spousal sexual violence victimization (31.1% physical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
2
17
0
4
Order By: Relevance
“…The study also found some evidence that physical IPV and/or sexual violence victimization was associated other health risk behaviours, such as an unhealthy diet (skipping breakfast and frequent salt intake), as found in a previous study [15]. Contrary to some previous investigations [5,15,[19][20][21][22][23], this study did not find an association between physical IPV and/or sexual violence victimization and physical inactivity, inadequate fruit and vegetable intake, not always wearing a seatbelt, poor self-rated health status, and poorer educational outcomes. In addition, some studies found an association between physical IPV and injury [5,10], while this study did not find this association.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The study also found some evidence that physical IPV and/or sexual violence victimization was associated other health risk behaviours, such as an unhealthy diet (skipping breakfast and frequent salt intake), as found in a previous study [15]. Contrary to some previous investigations [5,15,[19][20][21][22][23], this study did not find an association between physical IPV and/or sexual violence victimization and physical inactivity, inadequate fruit and vegetable intake, not always wearing a seatbelt, poor self-rated health status, and poorer educational outcomes. In addition, some studies found an association between physical IPV and injury [5,10], while this study did not find this association.…”
Section: Discussionsupporting
confidence: 49%
“…Several studies found that a history of physical IPV and/or sexual violence victimization among adolescents and emerging adults increased the odds for substance use, such as alcohol use or binge drinking [2,5,9,10,13], tobacco use [5,6], drug use [2,5,6,9,10,14], and substance use at last sex [3]. Other health risk behaviours include physical inactivity [5], eating unhealthy foods [15], such as inadequate fruit and vegetable intake [22], and not wearing a seatbelt [15]. Moreover, some studies found as a consequence of physical IPV and/or sexual violence victimization a poor self-rated health status [21,23], poor quality of life [19], and poorer educational outcomes [9,20].…”
Section: Introductionmentioning
confidence: 99%
“…A violência intrafamiliar esteve presente nos estudos como fator instigante na violação dos direitos do adolescente. A exposição à violência no seio familiar é comum entre os adolescentes, com destaque para famílias com menor poder aquisitivo que se encontram propensos a testemunhar e/ou experimentar esse descumprimento dos direitos da criança e do adolescente (32,39,(49)(50)(51)(52)(53). Ao indagar a respeito do motivo que leva os pais ou responsáveis a não exercerem sua função de proteção, observa-se que as ocorrências desses delitos podem ser justificadas pela tolerância social a esse tipo de fenômeno, pois a maioria dessas situações são negligenciadas, seja o adolescente como espectador ou vítima (25,26,32).…”
Section: Métodosunclassified
“…Pre-pregnancy BMI is related to the birth weight of the child and complications during pregnancy 2 . There is an increased risk of low birth weight 38 , foetal growth restriction (FGR) 4,5,9 , threatened preterm delivery, and preterm delivery 3,4,6,10 , and anaemia 3,11 in pre-pregnant underweight women when compared with those with normal weight before pregnancy. A meta-analysis 12 reported that women who gain less weight than that recommended by the Institute of Medicine (IOM) during pregnancy have increased risk of preterm delivery and small-for-gestational age (SGA) infants, while women who gain more weight than that recommended have an increased risk of foetal macrosomia, caesarean delivery, and large-for-gestational age (LGA) infants.…”
Section: Introductionmentioning
confidence: 99%